The resurrection of Mary Mabel McTavish - Stratton, Allan 1951- (Dundurn, 2014)
It's the Great Depression and Mary Mabel McTavish is suicidal. A drudge at the Bentwhistle Academy for Young Ladies (aka Wealthy Juvenile Delinquents), she is at London General Hospital when little Timmy Beeford is carried into emergency and pronounced dead. He was electrocuted at an evangelical road show when the metal cross on top of the revival tent was struck by lightning. Believing she's guided by her late mother, Mary Mabel lays on hands. Timmy promptly returns to life.William Randolph Hearst gets wind of the story and soon the Miracle Maid is rocketing from the Canadian backwoods to '30s Hollywood. Jack Warner, J. Edgar Hoover, and the Rockettes round out a cast of Ponzi promoters, Bolshevik hoboes, and double-dealing social climbers in a fast-paced tale that satirizes the religious right, media manipulation, celebrity, and greed